The impact of attitude toward COVID-19 vaccine on intention to receive influenza vaccination: a multi-group comparison based on the influence of presumed influence model and spillover effects - Zhang, Yun; Yi, Hongfa (Frontiers in Public Health, 2024)
Influenza vaccination is one of the most important strategies for preventing influenza. However, the influenza vaccination rate in China remains low. During the COVID-19 pandemic, people held different attitudes toward COVID-19 vaccine. In the post-pandemic era, do the varying attitudes toward COVID-19 vaccine affect intention to receive influenza vaccination? Based on the influence of presumed influence (IPI) model and spillover effects, this study employed structural equation modeling for multigroup comparison to analyze questionnaires from 613 participants, using instruments such as Perceived Media Influence on Others Scale(PMIO), Susceptibility to Influenza Scale(SI), and Attitude towards Influenza Vaccine Scale(AIV). The key findings are as follows: (1) Information exposure to influenza vaccine significantly influences perceived media influence on others. (2) Perceived media influence on others does not directly impact the intention to receive influenza vaccination but rather affects it through attitude towards influenza vaccine. (3) Moreover, multi-group analyses revealed differences in the IPI model among audiences with different attitudes toward COVID-19 vaccine. These differences demonstrated that prior attitude towards COVID-19 vaccine can influence attitude towards similar influenza vaccine, thus demonstrating the existence of spillover effects. Spillover effects of attitude to COVID-19 vaccine on intention to receive influenza vaccination are further discussed in this study.